Impacts of different intensities of exercise on inflammation and hypoxia markers in low altitude - Fatih Baygutalp (BMC, 2021)
Abstract Background This study aims to determine and compare the effects of exercise modalities with different intensities on the secretion of key inflammation and hypoxia markers in amateur athletes. Methods Twenty-three athletes with a mean age of 20.1 years, living at low altitude (1850 m) participated in this study. The participants' maximal oxygen consumption values (VO2 max) were determined with an incremental cycle exercise test as 54.15 ± 6.14 mL kg min−1. Athletes performed four protocols: at rest, 50% VO2 max, 75% VO2 max and 100% VO2 max (until exhaustion) with one-week intervals. 50% VO2 max, 75% VO2 max sessions were performed continuously for 30 min on a bicycle ergometer and 100% VO2 max session was performed by cycling until exhaustion. Blood samples were obtained at rest and immediately after each exercise session. Serum tumor necrosis factor alpha (TNF-α), C-reactive protein (CRP), interleukin-10 (IL-10), and hypoxia inducible factor-1 alpha (HIF-1α) levels were measured. Results There were significant differences in serum TNF-α levels in 75% VO2 max and 100% VO2 max sessions (489.03 ± 368.37 and 472.70 ± 365.21 ng/L, respectively) compared to rest conditions (331.65 ± 293.52 ng/L). Serum CRP levels of 50% VO2 max and 75% VO2 max sessions (1.19 ± 0.50; 1.07 ± 0.52 mg/L) were significantly higher than the rest condition (0.74 ± 0.35 mg/L). There were significant differences in serum IL-10 levels of rest condition and 50% VO2 max; 50% VO2 max, and 100% VO2 max sessions (328.09 ± 128.87; 446.36 ± 142.84; 347.44 ± 135.69; 324.88 ± 168.06 pg/mL). Serum HIF-1α levels were significantly higher in 75% VO2 max session compared to rest (1.26 ± 0.16; 1.08 ± 0.19 ng/mL) (P < 0.05 for all comparisons). Conclusions Both inflammatory and anti-inflammatory pathway is induced on different exercise intensities. Exercise protocols performed until exhaustion may lead to activation of inflammatory pathways and hypoxia-induced damage.